Ontogenic Expression And Characterization Of The Longchained Polyunsaturated Fatty Acid Biosynthesis Enzyme, Elongase In Zebrafish - Tan, Sze Huey (2012)

(untitled)
The importance of long-chained polyunsaturated fatty acids (LC-PUFAs) in vertebrates’ development has been widely studied. Among these, include roles in maintaining cellular membrane integrity, cellular signaling, gene regulation and metabolism. LC-PUFAs such as arachidonic acid, eicosapentaenoic acid and docosahexaenoic acid also mediate physiological processes like inflammation, immunity, reproduction and development. Despite the known importance of LCPUFAs during development, very little is known about their utilization and biosynthesis during embryogenesis.